A direct thrombin inhibitor studied by dynamic whole blood clot formation - Sørensen, Benny; Ingerslev, Jørgen (Thrombosis and Haemostasis, 2006)
Direct thrombin inhibitors have proven efficacious in prevention of venous thromboembolism. Bleeding complications are rare, but in case of acute serious bleeding, an effective and instant haemostatic intervention may be required. In the present study it was demonstrated that the direct thrombin inhibitor melagatran induces dose-dependent abnormalities in whole blood (WB) clotting profiles as recorded bya recently described modified thrombelastographic model, and that rFVIIa or APCC are capable of improving the haemostatic capacity. Experiments were performed using WB from 30 healthy males. In-vitro titration experiments (n=10) with addition of melagatran to WB corresponding to plasma concentrations ranging from 0 to 5.0 µM (12 steps) showed a dose-dependent prolongation of the clot initiation and characteristic decrease of the maximum rate of clot propagation. In-vitro intervention studies (n=20) were completed with four different concentrations of melagatran as well as addition of four different levels of rFVIIa or APCC. At all tested concentrations of melagatran, rFVIIa significantly shortened the melagatran-induced prolonged clot initiation but induced only minor improvements of the reduced clot propagation. In contrast, APCC significantly and dose-dependently shortened the clot initiation and accelerated the clot propagation. In conclusion, our thrombelastographic model appears useful for evaluating the effect of direct thrombin inhibitors on dynamic WB clot formation and rFVIIa, but especially APCC significantly improved theWB clot formation. The pronounced stabilizing effect of APCC may be caused by its content of prothrombin and activated coagulation factors.
Keywords: Melagatran; recombinant factor VIIa; activated prothrombin complex concentrate; thrombelastography